Phylogenetically Distinct Bacteria Involve Extensive Dechlorination of Aroclor 1260 in Sediment-Free Cultures - Wang, Shanquan; He, Jianzhong (PLOS ONE, 2013)
Microbial reductive dechlorination of the persistent polychlorinated biphenyls (PCBs) is attracting much attention in cleanup of the contaminated environment. Nevertheless, most PCB dechlorinating cultures require presence of sediment or sediment substitutes to maintain their dechlorination activities which hinders subsequent bacterial enrichment and isolation processes. The information on enriching sediment-free PCB dechlorinating cultures is still limited. In this study, 18 microcosms established with soils and sediments were screened for their dechlorination activities on a PCB mixture – Aroclor 1260. After one year of incubation, 10 out of 18 microcosms showed significant PCB dechlorination with distinct dechlorination patterns (e.g., Process H, N and T classified based on profiles of PCB congeners loss and new congeners formation). Through serial transfers in defined medium, six sediment-free PCB dechlorinating cultures (i.e., CW-4, CG-1, CG-3, CG-4, CG-5 and SG-1) were obtained without amending any sediment or sediment-substitutes. PCB dechlorination Process H was the most frequently observed dechlorination pattern, which was found in four sediment-free cultures (CW-4, CG-3, CG-4 and SG-1). Sediment-free culture CG-5 showed the most extensive PCB dechlorination among the six cultures, which was mediated by Process N, resulting in the accumulation of penta- (e.g., 236-24-CB) and tetra-chlorobiphenyls (tetra-CBs) (e.g., 24-24-CB, 24-25-CB, 24-26-CB and 25-26-CB) via dechlorinating 30.44% hepta-CBs and 59.12% hexa-CBs after three months of incubation. For culture CG-1, dechlorinators mainly attacked double flanked meta-chlorines and partially ortho-chlorines, which might represent a novel dechlorination pattern. Phylogenetic analysis showed distinct affiliation of PCB dechlorinators in the microcosms, including Dehalogenimonas and Dehalococcoides species. This study broadens our knowledge in microbial reductive dechlorination of PCBs, and provides essential information for culturing and stimulating PCB dechlorinators for in situ bioremediation applications.